2022
DOI: 10.1007/s00405-022-07441-4
|View full text |Cite
|
Sign up to set email alerts
|

Universal newborn hearing screening with automated auditory brainstem response (AABR) in Hungary: 5-year experience in diagnostics and influence on the early intervention

Abstract: Purpose In 2015 a new regulation and guidelines for the universal newborn hearing screening by AABR measurement have been implemented in Hungary. The aim of our study was to analyse (1) the past 5 years of data from our diagnostic centre about the incidence and types of congenital hearing losses, and (2) the first experiences with the National Newborn Hearing Screening Registry, started in 2019, and (3) the influence of the screening on the pediatric cochlear implant program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Among neonates with hearing loss, 4 neonates (33.4%) had unilateral profound SNHL, 3neonates (25%) had bilateral profound SNHL, 3 neonates (25%) had unilateral moderate SNHL, 1neonate (8.3%) had bilateral moderate SNHL and1 neonate (8.3%) received a diagnosis of auditory neuropathy. Gáborján et al (10) in their study about neonatal hearing screening in Hungary, using ABR in diagnosis stage they found that regarding the severity of the hearing loss (from 102 children) mild, moderate, severe and profound hearing loss were diagnosed in 12%, 31%, 9% and 48% respectively). Sabbagh et al (11) in their study about the neonatal hearing screening revealed that of 24 hearing-impaired newborns, (62.5%) had bilateral hearing loss and (37.5%) had unilateral HL where mild hearing loss (20-39 dB) was (12.5%) , moderate hearing loss (40-55 dB) in (20.8%) neonates, severe hearing loss (70-90 dB) in (37.5%), and profound hearing loss (>90 dB)in (29.2%) neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Among neonates with hearing loss, 4 neonates (33.4%) had unilateral profound SNHL, 3neonates (25%) had bilateral profound SNHL, 3 neonates (25%) had unilateral moderate SNHL, 1neonate (8.3%) had bilateral moderate SNHL and1 neonate (8.3%) received a diagnosis of auditory neuropathy. Gáborján et al (10) in their study about neonatal hearing screening in Hungary, using ABR in diagnosis stage they found that regarding the severity of the hearing loss (from 102 children) mild, moderate, severe and profound hearing loss were diagnosed in 12%, 31%, 9% and 48% respectively). Sabbagh et al (11) in their study about the neonatal hearing screening revealed that of 24 hearing-impaired newborns, (62.5%) had bilateral hearing loss and (37.5%) had unilateral HL where mild hearing loss (20-39 dB) was (12.5%) , moderate hearing loss (40-55 dB) in (20.8%) neonates, severe hearing loss (70-90 dB) in (37.5%), and profound hearing loss (>90 dB)in (29.2%) neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this is a viable solution for well babies, in a setup involving two-stage AABR protocol in high-risk newborns, this solutions becomes redundant. But recently, a study from Hungary reported using a third AABR test to reduce false-positive results following the two-stage AABR protocol [ 36 ]. Even though this could be a missing link in reducing false-positivity rate of two-stage AABR programs, implementing it on a larger scale might still not be cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Az objektív vizsgálatok minden életkorban fontos szerepet játszanak az audiológiai differenciáldiagnosztikában. Bizonyos életkorokban, például csecsemők és kisgyermekek esetében csak ilyen vizsgálatok alapján mondhatunk objektív véleményt a hallásról [16], így a szubjektív elemek kiküszöbölhetők. A stapediusreflex és az otoakusztikus emisszió mérésének indokolt esetekben minél szélesebb körben történő alkalmazása és értékelése az audiológiai differenciáldiagnosztikában ma már alapvető.…”
Section: áBraunclassified